Heat transfer in solar receiver heat exchanger with combined punched-V-ribs and chamfer-V-grooves - Promvonge, Pongjet; Skullong, Sompol (My University, 2019)
An experimental work has been carried out to investigate the influence of combined turbulence promoters (or turbulators) on forced convection and fluid flow resistance behaviors in a solar air heater duct. Two turbulators included V-ribs with punched holes and chamfered V-grooves were introduced. The V-rib and the V-groove having the attack angle of 45° were mounted repeatedly on the absorber plate with their arrangements for V-tip pointing upstream and pointing downstream. Air as the test fluid flowed into the duct with Reynolds number (Re) ranging from 5300 to 23,000. The rib parameters were three relative rib-pitches (RP = 1.0, 1.5 and 2.0), three inclination angles (β = 45°, 0° and −45°) of rib-punched holes having a single relative rib height or blockage ratio, RB = 0.5. The groove parameters included three relative groove-pitch lengths (RP = 1.0, 1.5 and 2.0) similar to the V-rib case. Influences of this newly designed absorber plate on Nusselt number (Nu) and friction factor (f) have been examined and compared with similar results of the smooth duct alone. The experimental results demonstrated that the combined turbulators at β = 45° and RP = 1.0 provide the maximum Nu and f, especially for the V-up case due to stronger vortex flows and the impinging flows from the punched holes over the absorber plate. Further, a new thermal enhancement factor (TEF) at similar pumping power has been proposed and it indicates that the combined V-up rib-groove with β = 45° and RP = 1.5 has the highest TEF of about 2.47.
Keywords: Punched-rib; Solar air heater; Thermal performance; V-groove; Vortex generators